The Influence of Leadership and Compensation on Work Motivation and its Impact on Nurse Performance - Agus Wahyudianto; Taufik Zulfikar; Etty Sofia Mariati Asnar (Journal La Medihealtico, 2026)
This study aims to analyze the influence of Leadership and Compensation on Work Motivation and its impact on Nurse Performance at RSUD Aji Muhammad Parikesit Tenggarong. In the context of healthcare services, the role of effective leadership and a fair compensation system are crucial factors in enhancing both the motivation and performance of nursing staff. This research employs a quantitative method with purposive sampling technique, involving 213 nurses working at RSUD Aji Muhammad Parikesit Tenggarong. Data were collected through structured questionnaires and analyzed using path analysis. The results of the study indicate that Leadership has a positive and significant influence on Work Motivation and Nurse Performance, both directly and indirectly through Work Motivation. Compensation also shows a positive effect on Work Motivation and Performance, with the indirect effect through Work Motivation being greater than the direct effect. Furthermore, Work Motivation has a significant influence on improving Nurse Performance. These findings provide practical implications for hospital management, particularly in developing more effective leadership programs and improving the compensation system to enhance nurse motivation and performance.